2014
DOI: 10.3906/bot-1305-19
|View full text |Cite
|
Sign up to set email alerts
|

Does gypsum influence seed germination?

Abstract: Flora inhabiting gypsum outcrops in arid environments shows a high level of specialization. However, the processes involved are still unclear, specifically at the key stage of germination. Here, to assess whether gypsum could chemically influence seed germination, we tested the germination of species according to 3 functional groups: gypsophiles, gypsovags, and calcicoles. A total of 24 taxa were selected, all occurring in gypsum and limestone substrates, under a semiarid and dry Mediterranean climate. Three l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 26 publications
0
11
0
Order By: Relevance
“…; Cañadas et al . ). Previous studies showed that gypsophiles have higher S, Ca and total ash content than gypsovags (Duvigneaud & Denaeyer‐De Smet ; Duvigneaud ; Boukhris & Lossaint , ; Palacio et al .…”
Section: Introductionmentioning
confidence: 97%
“…; Cañadas et al . ). Previous studies showed that gypsophiles have higher S, Ca and total ash content than gypsovags (Duvigneaud & Denaeyer‐De Smet ; Duvigneaud ; Boukhris & Lossaint , ; Palacio et al .…”
Section: Introductionmentioning
confidence: 97%
“…We hypothesized that (1) the germination of gypsophiles would be higher in natural gypseous soil and lower in the acidic soil; (2) gypsovags would show similar germination on soil with or without gypsum; and (3) owing to the similar germination responses observed in gypsophiles from the Iberian Peninsula and the Chihuahuan Desert (e.g. Cañadas et al, 2014;Secor and Farhadnejad, 1978), we expect the aforementioned trends would hold true regardless of geographic origin.…”
Section: Introductionmentioning
confidence: 99%
“…Some gypsum endemic species have also been shown to have a higher ability than co-occurring gypsovags to surpass the hard physical crust typical of gypsum soils at the seedling stage (Romão and Escudero, 2005). The distribution of plants on gypsum soils could also be linked to a differential ability to germinate on gypsum (Romão and Escudero, 2005), since calcium and gypsum concentration can affect seed germination, also in gypsophile species (Anderson, 1982; Cañadas et al, 2014; Merlo et al, 1997; Secor and Farhadnejad, 1978).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…struthium is one of the most abundant gypsophytes in Spain, and is exclusive of gypsum soils. It is specifically adapted to gypsum, which even has a positive effect on the germination of its seeds (Cañadas et al 2013). This species is endemic in the SE Iberian Peninsula, with a wide distribution in the C, E and S, in the Murcian-Almerian, Balearic-Catalonian-Provençal, Baetic and Mediterranean Central Iberian biogeographic provinces.…”
Section: Introductionmentioning
confidence: 99%